Síndrome de Burnout y rendimiento académico en estudiantes de la Carrera de Laboratorio Clínico de la Universidad Nacional de Loja - Quezada Ordóñez, Alex Fabián (2022)
Burnout Syndrome is an inappropriate response to chronic work stress, characterized by emotional exhaustion, depersonalization and student incompetence at the university level, which may impair their performance. The present research is derived from a macro project that seeks to relate Burnout Syndrome and academic performance in the Faculty of Human Health of the National University of Loja, and that for this study was developed in the career of Clinical Laboratory, which aims to determine the Burnout Syndrome and academic performance, identify the presence of Burnout Syndrome, determine academic performance, establish the relationship between Burnout Syndrome and academic performance, and establish the relationship between Burnout Syndrome and academic performance, determine academic performance, establish the relationship between Burnout Syndrome and academic performance, and recognize the academic cycle with greater presence of the syndrome, it is a study with a qualitative, descriptive, cross-sectional, correlational approach, with a sample of 83 students who met inclusion and exclusion criteria, Maslach's Burnout Inventory was applied. The results obtained showed the prevalence of Burnout in 14.5% of students, being higher in the sixth cycle; regarding academic performance, 54.76% have a very good average and of the total number of students who presented Burnout, 50% have this average. According to Pearson's correlation with a value of 0.112 and a bilateral significance of 0.314, there is no relationship between Burnout and academic performance, accepting the null hypothesis